2009
DOI: 10.2337/dc09-0094
|View full text |Cite
|
Sign up to set email alerts
|

Costs to Medicare of the Informatics for Diabetes Education and Telemedicine (IDEATel) Home Telemedicine Demonstration

Abstract: OBJECTIVETo estimate the impacts on Medicare costs of providing a particular type of home telemedicine to eligible Medicare beneficiaries with type 2 diabetes.RESEARCH DESIGN AND METHODSTwo cohorts of beneficiaries (n = 1,665 and 504, respectively) living in two medically underserved areas of New York between 2000 and 2007 were randomized to intensive nurse case management via televisits or usual care. Medicare service use and costs covering a 6-year follow-up period were drawn from claims data. Impacts were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 6 publications
0
35
0
3
Order By: Relevance
“…77,78 However, the extensiveness and the complexity of the system, as well as difficulties in its use reported by the consortium and the expensive sets of sensors and hardware installed in participants' homes certainly contributed to this result. It should also be assumed that the high costs of the telemedicine group could be related to the fact that the system was implemented in a medically underserved group of patients, with low social and intellectual status, thus not being representative for the entire group of patients with diabetes.…”
mentioning
confidence: 99%
“…77,78 However, the extensiveness and the complexity of the system, as well as difficulties in its use reported by the consortium and the expensive sets of sensors and hardware installed in participants' homes certainly contributed to this result. It should also be assumed that the high costs of the telemedicine group could be related to the fact that the system was implemented in a medically underserved group of patients, with low social and intellectual status, thus not being representative for the entire group of patients with diabetes.…”
mentioning
confidence: 99%
“…For several HTU functions, Cohort 1 participants took longer than their Cohort 2 counterparts to use their HTUs for the first time. For example, the median amounts of time for monitoring and uploading clinical readings were substantially higher for Cohort 1: 284 versus 179 days after installation for monitoring, and 19 versus 3 days for uploading (Moreno et al, 2005). In contrast, the median time to first measurement of blood sugar or blood pressure was the same for both cohorts (1 day), as was the time from HTU installation to the first televisit (23 and 21 days, respectively).…”
Section: Htu Learning Curves and Frequency And Intensity Of Usementioning
confidence: 69%
“…Thus, in the IDEATel study, which started in 2000, health care costs increased 71% to 116% in the intervention group compared with the control group. 42 The costs associated with the intervention arm, more than $8000 per patient per year, were driven mainly by the cost of a specialized home telemedicine unit and associated training and demonstrating costs. 42 However, as early as 2003, Jansa and colleagues 36 reported that, in the absence of technical problems, IBGMS use was associated with a decrease in health care provider costs of V40 (w$55 US) per case over 12 months, because of decreased lengths of appointments in the intervention group.…”
Section: Cost-effectiveness Of Internet Blood Glucose Monitoring Systemsmentioning
confidence: 99%